How Far Is The Community Involved in Structuring Sustainable Settlements in Indonesia? - Fadli, Yusuf; Sarofah, Riska (Universitas Diponegoro, Indonesia, 2021)
This Study describes community involvement in the development planning process through the community action plan program. The case study in this research takes the process of structuring the Bukit Duri village in South Jakarta, Indonesia. In this study, the method used is qualitative with in-depth interviews, online media content analysis and data processing using the Nvivo 12+ application. The object of research is whether the Community Action Plan (CAP) program can provide solutions to the residents of Bukit Duri and what is the role of the actors involved in implementing the Community Action Plan (CAP) program. The results showed that the Community Action Plan (CAP) program was not successful in being implemented in Bukit Duri, South Jakarta due to the lack of a collaborative process from related parties such as citizens, government and civil society. Other obstacles in implementing the program include the availability of land, legality, and community commitment. Future research is expected to be able to discuss alternative policies taken by the government after the failure of implementing the community action plan.